1989
DOI: 10.2118/16345-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Application of a Composite Reservoir Model to Pressure-Transient Analysis

Abstract: This paper presents analytical solutions for interpreting pressure-transient tests for wells producing from a finite composite reservoir system. The paper also includes rate solutions and methods for analyzing long-term production data and forecasting production of oil or gas in a finite composite reservoir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In practice, the first semilog straight line may be masked by wellbore storage, whereas the second straight line may not have been reached or may be superseded by boundary effects, thus making the intersection-time method often inapplicable. Another method uses type-curve matching of well-test pressure and pressure-derivative data (Olarewaju and Lee 1989;Olarewaju et al 1991). The pressure match can be used to calculate the inner-region mobility: …”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the first semilog straight line may be masked by wellbore storage, whereas the second straight line may not have been reached or may be superseded by boundary effects, thus making the intersection-time method often inapplicable. Another method uses type-curve matching of well-test pressure and pressure-derivative data (Olarewaju and Lee 1989;Olarewaju et al 1991). The pressure match can be used to calculate the inner-region mobility: …”
Section: Appendix Amentioning
confidence: 99%
“…Interpretation of gas/condensate pressure-transient data that exhibit a two-or a three-region radial composite behavior yields the effective reservoir permeability, the wellbore skin effect, and the mobility or permeability ratios between the various regions [using straight-line analysis (Brown 1985)-see Appendix B-or typecurve matching (Olarewaju and Lee 1989)]. The storativity ratio between two adjacent regions, however, cannot be uncoupled from the radius because analytical well-test-analysis methods can only account for one set of pressure/volume/temperature (PVT) data, yet both are needed to estimate the total skin effect.…”
Section: Introductionmentioning
confidence: 99%
“…Issaka and Ambastha (1996) developed a generalised pressure derivative formula for a composite reservoir to identify the flow regimes in four flow geometries (radial, elliptical, linear and spherical). Olarewaju and Lee (1989) found that the pressure derivative curves for a composite reservoir show a different response from homogeneous reservoirs. Jokhio et al (2001) and Hachlaf et al (2002) extended the Tiab's direct synthesis technique to analyse injection and fall off tests in water injection wells, and the problem was described and solved as a composite reservoir.…”
Section: Introductionmentioning
confidence: 98%
“…According to the concept of composite reservoir, when there is a discontinuity in the material properties in the radial direction from a well, the reservoir can be regarded as a composite reservoir [26][27][28]. Considering that acid fracturing creates a high permeability zone near the wellbore, the case of a well with wormholes and artificial fractures in FVCRs can be represented by a composite reservoir.…”
Section: Introductionmentioning
confidence: 99%